Ultrasound Examination of Thyroid Cancer - Vlasyk , Marharyta; Romanenko , Hanna (The Ukrainian Scientific Medical Youth Journal, 2023)
according to statistics in Ukraine, the thyroid cancer incidence is about 11 per 100,000 people in the capital region, 6 per 100,000 in other districts. Women are more often affected than men (4:1); it is mainly found in patients aged 40-55 years. After the accident at the Chernobyl nuclear power plant, there was an increase in the number of patients with thyroid cancer, especially among children under the age of 15 (boys - 4% and girls - 9%).